Analisis Kemampuan Literasi Dasar Siswa Kelas 1 SDN Karangtempel - Vena Antra Laksana, Ade; Prima Artharina, Filia; Wijayanti , Arfilia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Basic literacy is a competency that students must possess from the elementary school level because it serves as a foundation for developing thinking skills, understanding information, communicating, and solving problems in learning. This study aims to describe the basic literacy skills of first-grade students at SDN Karangtempel and identify the factors that influence their development. The study employed a descriptive qualitative approach with 18 first-grade students, the principal, and the classroom teacher as research subjects. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that students’ basic literacy skills varied across indicators. Print awareness and vocabulary mastery were the most developed indicators, while alphabet knowledge, reading comprehension, and speaking skills were still relatively low. In numeracy, most students were able to use basic numbers and mathematical symbols but still experienced difficulties in analyzing and interpreting simple information. To improve these abilities, the school implemented literacy habituation activities through reading before lessons and additional guidance for students who still experienced difficulties. Literacy development was influenced by internal factors, such as motivation and learning interest, as well as external factors, including parental support, teacher guidance, peer influence, and learning facilities.